2018
DOI: 10.4103/jips.jips_326_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mangosteen peel extract combined with demineralized freeze-dried bovine bone xenograft on osteocalcin, collagen 1, and osteoblast as alveolar bone regeneration in socket preservation

Abstract: The administration of mangosteen peel extract combined with DFDBBX as a means of tooth extraction socket preservation can increase osteocalcin and collagen 1 expression. Consequently, osteoblasts as a means of alveolar bone regeneration will increase in number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Osteocalcin can also be used as a biomarker in accurately evaluating the bone formation process. [ 13 14 ] As a result, this research aimed to analyze the role of a combination of Moringa leaf extract and DFDBBX for tooth extraction sockets preservation in generating osteocalcin, TGFβ1, and osteoblast expression.…”
Section: Introductionmentioning
confidence: 99%
“…Osteocalcin can also be used as a biomarker in accurately evaluating the bone formation process. [ 13 14 ] As a result, this research aimed to analyze the role of a combination of Moringa leaf extract and DFDBBX for tooth extraction sockets preservation in generating osteocalcin, TGFβ1, and osteoblast expression.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it can potentially increase osteocalcin and collagen 1 expressions, thereby accelerating alveolar bone regeneration. [ 16 17 ] Another study showed that a combination of xenograft and Moringa leaf extract can effectively generate TGF-β1 and osteocalcin expressions during the preservation of tooth extraction sockets. [ 18 ] The increase in osteoblast cells in this study was strongly induced by the combination of propolis extract and BBG.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alveolar ridge height is important for the retention and stabilization that constitute prerequisites to successful dental treatment. Therefore, tissue engineering for socket preservation is essential (Kresnoadi et al, 2018), while vascularization also constitutes an important factor in wound healing (Schiff, 2009).…”
Section: Journal Ofmentioning
confidence: 99%
“…Production of histopathological C. cobaya socket samples was completed at the Dr. Soetomo Anatomical Pathology Laboratory, Surabaya using Hematoxylin-Eosin (HE) stain to observe blood vessels and macrophages (Kresnoadi et al, 2018), while Masson Trichrome (MT) stain was employed to enable observation of collagen density (Rachmanita et al, 2019). The samples were subsequently examined by means of a light microscope (Shimadzu®, Japan) at 400x magnificationin order to establish the number of new blood vessels and macrophages present in the socket.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation